Associação de variedades de goiaba, bioinseticidas e o parasitóide Diachasmimorpha longicaudata no controle de Anastrepha fraterculus - Oliveira, Flávia Queiroz de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The generation of information about the potential of alternative tactics in the control of fruit flies has attracted a growing interest, both producing and researchers. This research aimed to evaluate the effects of guava cultivars and substances from plant metabolism on biological parameters of Anastrepha fraterculus (Wied., 1830) (Diptera: Tephritidae) and Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae). The study was conducted in the Laboratory of Plant Resistance, Department of Plant Protection, Faculty of Agricultural Sciences and Veterinary Medicine - UNESP. The guava fruits were obtained from Company Val fruits, located in “Vista Alegre do Alto” - SP. The fruit-flies and parasitoids were derived from rearing on artificial diet in the laboratory Radioentomologia - CENA. 6 bioassays were conducted: 1- Determining the maturity stage of guava fruits preferred for egg-laying of A. fraterculus, 2- No preference for egg-laying of A. fraterculus fruits of the guava cultivars, 3- Effect of natural products used in guava fruit on egg-laying of A. fraterculus, 4- Association of the effects of the fruits of guava cultivars and natural products on parasitism of D. longicaudata, 5- Antibiosis test of fruit varieties of guava and on A. fraterculus and 6- Effect of extrinsic resistance of cultivars of guava fruit on the parasitoid D. longicaudata. Fruits were treated with the following products: neem oil, essential oil from fennel and citronella, and controle. Tests with and without choice has been made. The results were subjected to analysis of variance (ANOVA), means were compared by Tukey test (P = 0.05). A. fraterculus female prefer stadiums semi-ripe and ripe for egg-laying. The Século XXI cultivar is more susceptible to attack by A. fraterculus. Products which showed the lowest infestation rates were oils of neem and citronella, from the 1.0% concentration. The fruits when ...

A geração de informações sobre o potencial de táticas alternativas no controle de moscas-das-frutas tem despertado crescente interesse, tanto dos produtores quanto dos pesquisadores. Esta pesquisa teve como objetivo avaliar os efeitos de variedades de goiaba e de substâncias de origem vegetal sobre parâmetros biológicos de Anastrepha fraterculus (Wied., 1830) (Diptera:Tephritidae) e sobre o parasitóide Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae). A pesquisa foi realizada no Laboratório de Resistência de Plantas do Departamento de Fitossanidade da Faculdade de Ciências Agrárias e Veterinária - UNESP. Os frutos de goiaba foram adquiridos da Empresa Val frutas, localizada no município de Vista Alegre do Alto-SP. As moscas-das-frutas e os parasitóides foram oriundos de criação mantida em dieta artificial no Laboratório de Radioentomologia do CENA. Foram realizados 6 bioensaios: 1. Determinação do estágio de maturação dos frutos de goiaba preferidos para oviposição de A. fraterculus 2. Não preferência para oviposição de A. fraterculus por frutos de variedades de goiaba; 3. Efeito de produtos naturais aplicados em frutos de goiaba na oviposição de A. fraterculus; 4. Associação dos efeitos dos frutos de variedades de goiaba e de produtos naturais no parasitismo de D. longicaudata; 5. Teste de antibiose em A. fraterculus criadas em frutos de variedades de goiaba e 6. Efeito da resistência extrínseca de frutos de variedades de goiaba sobre o parasitóide D. longicaudata. Os frutos foram tratados com os seguintes produtos: óleo de nim, óleo essencial de erva-doce, óleo essencial de citronela, e teste padrão com água. Foram realizados testes com e sem chance de escolha. Os resultados foram submetidos à análise de variância (ANOVA), as médias foram comparadas pelo teste de Tukey (P = 0,05). Fêmeas de A. fraterculus preferem os estádios ...
Keywords: Goiaba - Doenças e pragas - Controle biológico; Mosca-das-frutas; Produtos naturais; Plantas - Resistência aos insetos; Inseticidas biológicos; Fruit-flies